Contraception of emergency in nursing education / formation: a documental study - Juliana Calazans de Cerqueira; Jacqueline Oliveira de Carvalho; Adriana Lemos (O Mundo da Saúde)
Having or not having a child is a human right since the 90’s. Emergency Contraception (EC) is a vital ally to ensure this right. However, lack of knowledge about his mechanism on the part of the population, among other factors, creates barriers to the use of CE as a contraceptive method. The objective was to identify the contents related to emergency contraception in the syllabus of colleges, in Rio de Janeiro State, and relate them to documents prepared by the Brazilian Ministry of Health on emergency contraception. This was a descriptive study. We analyzed disciplines Programs of nursing courses from selected colleges. The colleges have studied issues related to emergency contraception, but have almost no documents of the Brazilian Ministry of Health in their references, as well as on the specific subject. We concluded that to guarantee the access to emergency contraception is to guarantee rights and an assistance equanimity and in integral agreement to the principles and guidelines of the Unified Health System.